Become ITIL® 4 Foundation certified in 7 days : understand and prepare for the ITIL Foundation exam with real-life examples - Kaiser, Abhinav Krishna (Apress, 2021)
Use this guide book in its fully updated second edition to study for the ITIL 4 Foundation certification exam. Know the latest ITIL framework and DevOps concepts. The book will take you through the new ITIL framework and nuances of the DevOps methodology. The book follows the topics included in the foundation certification exam syllabus and includes new sections on ITIL's guiding principles, service value chain, and the four dimensions of service management. Also included are the concepts, processes, and philosophies used in DevOps programs and projects. ITIL and DevOps concepts are explained with relevant examples. By the time you finish this book, you will have a complete understanding of ITIL 4 and will be ready to take the ITIL 4 Foundation certification exam. You will know the DevOps methodology and how ITIL reinforces the philosophy of shared responsibility and collaboration. Over the course of a week, even while working your day job, you will be prepared to take the exam. You will: Know the basics of ITIL as you prepare for the ITIL Foundation certification exam Understand ITIL through examples Be aware of ITIL's relevance to DevOps and DevOps concepts.